1992
DOI: 10.1210/endo.131.6.1280207
|View full text |Cite
|
Sign up to set email alerts
|

A chimeric analog of human and salmon calcitonin eliminates antigenicity and reduces gastrointestinal disturbances.

Abstract: The minimum region in salmon calcitonin (sCT) which induces antigenicity and gastrointestinal disturbances has been identified by examining the cross-reactivity of several sCT fragments and CT analogs with antisera from sCT-treated patients, and by examining inhibition of gastrointestinal motility of these sCT fragments and CT analogs in conscious dogs. Sixteen residues at the N-terminus of sCT comprised the minimum fragment capable of inducing both activities. Human CT (hCT) showed no antigenicity and a four-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…To identify immunodominant epitopes, we analyzed five different therapeutic proteins for which evidence of immunogenicity exists in humans, namely, hGH, calcitonin, insulin, IFN-␤, and Epo (5,6,24,42,43). Although insulin and calcitonin did not contain any clear degenerate binding regions, four, six, and four degenerate binding regions were identified within the hGH, IFN-␤, and Epo proteins, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…To identify immunodominant epitopes, we analyzed five different therapeutic proteins for which evidence of immunogenicity exists in humans, namely, hGH, calcitonin, insulin, IFN-␤, and Epo (5,6,24,42,43). Although insulin and calcitonin did not contain any clear degenerate binding regions, four, six, and four degenerate binding regions were identified within the hGH, IFN-␤, and Epo proteins, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Studies with salmon calcitonin peptide fragments and chimeric calcitonin species suggest that the antigenic epitope is located in the sequence of Gly 10 -Lys-Leu-Ser-GlnGlu 15 (20), an epitope not apparently shared by human calcitonin which differs at four of the six residues in this stretch. The foreign specificity of the antibody response to salmon calcitonin is further supported by the findings that antibodies to salmon calcitonin showed no cross-reactivity with human calcitonin (20), and that patients with neutralizing antibodies to salmon calcitonin still responded to the human calcitonin therapy (21,22). This information indicates that the immunogenic response to salmon calcitonin is intrinsic to the amino acid sequence of this peptide which determines a foreign epitope.…”
Section: Product-related Factors Pertaining To Immunogenicitymentioning
confidence: 96%
“…It has also been suggested that residues of the Cterminal half of sCt are important for binding to the rat C1a, C1b and to the hCt receptors. Interestingly, the chimeric analog ACT-15 ((1-16)hCt/(17-32)sCt) shows a similar in vivo bioactivity to sCt in animal models, at the same time being devoid of the antigenicity and the gastrointestinal side effects of sCt [75][76][77][78].…”
Section: Structure-activity Relationships Of the Cts From Different Smentioning
confidence: 99%
“…Due to the high potency of sCt, this molecule became the main Ct to be used therapeutically to date [11,78]. There is however a low degree of homology between sCt and hCt (50%), which may cause the antigenic effects that are observed during the therapeutic application of sCt-based drugs, and that may be related to the observed "secondary resistance" or desensitization towards sCt [75][76][77][78]. The development of hCt-based agonists that by maintaining a high sequence similarity to hCt, exhibit high bioactivity has become an important target of biomedical research.…”
Section: Structure-activity Relationships Of Conformationally Constramentioning
confidence: 99%